2012 IEEE International Conference on Systems, Man, and Cybernetics (SMC) 2012
DOI: 10.1109/icsmc.2012.6378087
|View full text |Cite
|
Sign up to set email alerts
|

Therapist-centred design of NUI based therapies in a neurological care hospital

Abstract: Through a participatory design (PD) process with therapists at a neurological chronic care hospital that has no ICT based workflow processes we identified three main components where NUI technology can be deployed for physical therapy: patient stimulation, on-demand patient therapy tool control, and data logging and visualization. Based on our study, we created a scenario that encompasses these components for a specific physical therapy activity targeting head and torso movement for children suffering neurolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…The GUI uses symbols on a screen (e.g. folders or icons) that can be selected using a mouse, whereas an interface that relies on direct interaction such as touch, motion or speech is considered to be the Natural User Interface (NUI) [44].…”
Section: Death Of the Graphical User Interface (Gui)mentioning
confidence: 99%
“…The GUI uses symbols on a screen (e.g. folders or icons) that can be selected using a mouse, whereas an interface that relies on direct interaction such as touch, motion or speech is considered to be the Natural User Interface (NUI) [44].…”
Section: Death Of the Graphical User Interface (Gui)mentioning
confidence: 99%
“…By the end of this cycle, reports with interviews and observations, photos, movies, stories shading and creating scenarios were generated as artifacts. The research team involved in this first cycle reported their experiments and materials generated in dissertations and articles [1,3,6,4,5,7,8,10,11]. The second cycle of activities involved analysis of the collected requirements and their validation through interviews.…”
Section: Figure 1 Activities Of Interaction Designmentioning
confidence: 99%
“…Several prototypes were developed, refined and validated. Researchers created prototypes for the areas of Education [11], Nursing Care [1,2] and Physiotherapy [5] and during the validation, some solutions of interaction design were proposed and the prototypes were re-evaluated. In the third cycle the designers proposed some evaluations and usability tests, thus, improving the prototypes or generating new ones, by considering user's skills and technological innovations.…”
Section: Figure 1 Activities Of Interaction Designmentioning
confidence: 99%
“…In these contexts, often the person being cared for only receives a quality of care that depends upon the quality of treatment and procedures of the care workers. Our research is looking at these healthcare workers by focusing on their complex workflows to design applications and systems to integrate into their existing natural collaborative practices [2,3], considering their cultural values that shapes their relationship.…”
Section: Introductionmentioning
confidence: 99%
“…The three main findings are: 1.Supporting worker social and professional behaviour based on communication and workflow using an online social intranet is effective, 2.Designing for cultural based values appropriation as well as adoption is important and 3.Public workflow visualization can influence worker behavior considering cultural values. We believe that working with these professionals is an opportunity to design information technology based workflow that avoids a Windows, Icons, Menus and Pointers (WIMP) oriented strategy [3]. Likewise, we can use their workflow as a starting point in deciding what natural is for that cultural ecosystem, given that their workflow has evolved over more than two decades of practice [2].…”
Section: Introductionmentioning
confidence: 99%